Yoghurt Fortified Formulation of Lakum Fruit (Cayratia trifolia (L.) Domin) Extract as an Antioxidant - Weni Puspita; Nurkhasanah Nurkhasanah; Ika Dyah Kumalasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Lakum (Cayratia trifolia (L.) Domin) contains a lot of anthocyanin. Anthocyanin in Lakum fruit has a high stability if stored at low temperatures, acidic conditions, and without light. The acidic product such as yogurt can provide an optimum condition for anthocyanin stability and antioxidant activity. The purpose of this study was to optimize yogurt formulation fortified by lakum fruit extract as an antioxidant according to the requirements of the Indonesian National Standard (SNI). Lakum fruit extract was formulated in yogurt with various concentrations at 0%, 5%, 7.5% and 10%. Evaluations were carried out including tests of physical, chemical and microbiological properties and anthocyanin test and antioxidant of yogurt. The results showed that the yogurt formula fortified lakum fruit extract at 7.5% concentration resulted highest anthocyanin stability and antioxidant activity that fulfilled SNI requirements and the preferred level of respondents' preference with anthocyanin levels of 53.35±1.04 mg/L, antioxidant activity 69.15±0.24%, t90 7.97 days, total of lactic acid bacteria (LAB) 48.2x107 colony/gram, fat 3.72±0.03%, pH 3.87±0.03, total acid 0.83±0.06%, viscosity 639.07±2.06 cP, protein of 4.90±0.11%, hedonic test, 6.88 (like), and organoleptic purple (5), the distinctive aroma of lakum fruit (4.95), sour taste (4.85), fine texture (4.9) and slightly liquid viscosity (4.85).